Modification of Lime-Fly Ash-Crushed Stone with Phosphogypsum for Road Base - Hao Zhang; Yuan Cheng; Lei Yang; Weikang Song (Advances in Civil Engineering)
In order to increase the recycling of phosphogypsum waste, this study explored the feasibility of using phosphogypsum to replace some of the lime and aggregate in the lime-fly ash-crushed stone mixture which is a widely used road base material in China. For this purpose, compaction, compressive strength, composition structures, wetting-drying cycle tests, and shrinkage tests were carried out on the lime-fly ash-phosphogypsum-crushed stone composite to investigate its performance. The results indicate that lime-fly ash-crushed stone modified with phosphogypsum has the required strength of the road base material and favourable performances in environment (wetting-drying cycle) stability. The image processing analysis and shrinkage tests demonstrated that phosphogypsum can significantly improve the compactness and shrinkage performance of lime-fly ash-crushed stone mixture. A suitable content of phosphogypsum and a reasonable content of fine aggregate are conducive to improving the roadway engineering properties (i.e., decreasing shrinkage cracks and increasing compressive strength) of lime-fly ash-phosphogypsum-crushed stone composites.